Molecular Docking and QSAR Study of 5-O-acylpinostrobin Derivatives as Topoisomerase IIα Inhibitors - Rahmah, Siti; Widiandani, Tri; Ekowati, Juni; Adi Priatna, Puja (Universitas Airlangga, 2024)
Background: Cancer is one of the top causes of death worldwide. A wide range of illnesses known as cancer can start in almost any organ or tissue in the body when abnormal cells multiply uncontrollably. Cancer patients have higher levels of the Topo IIα protein in their cells, this protein has been proposed as a relevant target for anticancer treatment development. Objective: This study aims to predict the anticancer activity of pinostrobin and 5-O-acylpinostrobin derivatives against topoisomerase IIα by docking molecular and QSAR study. Methods: In silico analysis was performed using the structure of the topoisomerase IIα (PDB: 5GWK)) as templates. Molecular docking analysis was performed with AutoDock Vina. Result: All 5-O-acyl pinostrobin derivatives, showed lower ΔG values than the parent pinostrobin. The 5-O-acetyl pinostrobin compound showed the highest score, namely -9.14 kcal/mol. 5-O-acetyl pinostrobin is predicted as the most powerful inhibitor that can cause inhibition of topoisomerase IIα. Conclution: The results of the best QSAR equation obtained can be used as a reference for predicting the activity of the new pinostrobin derivatives to be synthesized by inserting the electronic (Etot) parameter values of the compounds into the equation.